SURGICAL TREATMENT FOR DISTAL BLOCKS CHOLEDOCHUS IN PATIENTS WITH MALIGNANT JAUNDICE - D. E. Zdzitovetsky; A. C. Kovalev (Креативная хирургия и онкология)
The article presents the surgical treatment of patients with distal unit choledochus. It was proposed the modified biliary drainage for recognizing drainage, which improves patient outcomes.